Molecular investigation of the pine‐tree lappet moth Dendrolimus pini (L.) population in Scotland: a new arrival or an old acquaintance?. (12th August 2021) - A'Hara, Stuart; Moore, Roger; Cottrell, Joan
Abstract: Pine‐tree lappet moth ( Dendrolimus pini L.) larvae can be serious defoliators of pine in several countries within mainland Europe. A breeding population of pine‐tree lappet moth was confirmed near Inverness, Scotland in 2009, prior to which the species had only been observed in the United Kingdom as an occasional nonbreeding migrant to southern England. To investigate whether a geographic pattern of DNA variation exists that could elucidate whether the population is native or introduced, we analysed nuclear (ITS2) and mitochondrial (NAD and COI) sequence data from D. pini from across a broad geographic range. Additionally, microsatellite marker data were used to examine neutral genetic diversity and to look for evidence of a recent population bottleneck in the Scottish population. ITS2 sequence analysis confirmed that the Scottish population was D. pini and identified a distinct Western European group of D. pini samples. Analysis of the mitochondrial sequences grouped the haplotypes into two main phylogenetic groups (A and B) and a well‐supported Western European sub‐group (b1). A high number of unique haplotypes were recorded, highlighting the haplotype diversity across the species range. The Scottish haplotype did not have an exact match but grouped with haplotypes from group B. The microsatellite markers highlighted low genetic diversity in the Scottish population but there was no evidence of a recent population bottleneck. Evidence to distinguish between a native versus a recent introduction origin of the Scottish population is equivocal. Further sampling to increase haplotype coverage may help to clarify this question.